2017
DOI: 10.1128/aac.02288-16
|View full text |Cite
|
Sign up to set email alerts
|

Enterocin AS-48 as Evidence for the Use of Bacteriocins as New Leishmanicidal Agents

Abstract: We report the feasibility of enterocin AS-48, a circular cationic peptide produced by Enterococcus faecalis, as a new leishmanicidal agent. AS-48 is lethal to Leishmania promastigotes as well as to axenic and intracellular amastigotes at low micromolar concentrations, with scarce cytotoxicity to macrophages. AS-48 induced a fast bioenergetic collapse of L. donovani promastigotes but only a partial permeation of their plasma membrane with limited entrance of vital dyes, even at concentrations beyond its full le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 73 publications
0
57
2
2
Order By: Relevance
“…The determination of viable bacteria after treatment with EMB and AS-48 resulted in a reduction of CFU counts between 90 and 99.9% in comparison with totals in untreated controls. The efficacy of AS-48 for killing intracellular pathogens was previously proven by Abengózar et al (14) when they showed the anti-leishmanial activity of AS-48 in Raw 264.7 infected macrophages. Despite the fact that the infection mechanism is different between Leishmania and mycobacteria, these experiments show that AS-48 is active against pathogens residing intracellularly in macrophages.…”
Section: Figmentioning
confidence: 80%
“…The determination of viable bacteria after treatment with EMB and AS-48 resulted in a reduction of CFU counts between 90 and 99.9% in comparison with totals in untreated controls. The efficacy of AS-48 for killing intracellular pathogens was previously proven by Abengózar et al (14) when they showed the anti-leishmanial activity of AS-48 in Raw 264.7 infected macrophages. Despite the fact that the infection mechanism is different between Leishmania and mycobacteria, these experiments show that AS-48 is active against pathogens residing intracellularly in macrophages.…”
Section: Figmentioning
confidence: 80%
“…A few select bacteriocins showed some potential as antiviral agents, as plant growth promoters, and as anti-cancer agents ( Drider et al, 2016 ). Recently, it was reported that enterocin AS-48 showed promising bioactivity against the protozoan parasites of the genera Leishmania ( Abengózar et al, 2017 ) and Trypanosoma ( Martínez-García et al, 2018 ).…”
Section: Applications Challenges and Prospectsmentioning
confidence: 99%
“…Recently, E. faecalis DD14 was isolated from meconium ( 5 ) and characterized for its Clostridium perfringens leaderless two-peptide bacteriocin designated enterocin DD14 ( 6 ). Enterocins are safe bacteriocins ( 7 ) with possible applications as food additives and antibiotic-complementary and leishmanicidal agents ( 8 11 ).…”
Section: Genome Announcementmentioning
confidence: 99%